2017
DOI: 10.1386/jpme.1.3.331_1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating popular music into urban schools: Examining students’ outcomes of participation in the Amp Up New York City music initiative

Abstract: This study is an examination of the influence of the Amp Up New York City (Amp Up NYC) music initiative on the development of students’ musical skills, social and emotional skills, and college and career-ready skill development. A retrospective pre-test survey was used to measure students’ self-assessment of their skill development. Surveys were also administered to their music teachers, classroom teachers, principals and parents. Student focus group interviews and classroom observations were also used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…From a broader perspective, students who participate in modern band programs report that their participation has positively affected their musical, social, emotional, and academic skill development (Weiss et al, 2017). Additionally, students also reported that participating in modern bands helped with interpersonal skills such as resolving conflicts with friends, collaborating with their classmates, and working well with other students (Abeles et al, 2021).…”
Section: Perspectives Of Modern Band Student Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a broader perspective, students who participate in modern band programs report that their participation has positively affected their musical, social, emotional, and academic skill development (Weiss et al, 2017). Additionally, students also reported that participating in modern bands helped with interpersonal skills such as resolving conflicts with friends, collaborating with their classmates, and working well with other students (Abeles et al, 2021).…”
Section: Perspectives Of Modern Band Student Participantsmentioning
confidence: 99%
“…As music teachers look to engage more students in school music, the teachers themselves are seeking out opportunities for professional development focused on popular music pedagogies and modern bands. Teachers participating in modern band professional development reported improved aural skills, stronger orientation toward student-centered learning experiences, and reengaging with music making for fun (Davis, 2018;Weiss et al, 2017). The skills learned through participation in a modern band professional development are transferable to the classroom setting (Dorfman, 2020) for teachers looking to incorporate songwriting and relevant and meaningful music experiences (Vasil, 2015).…”
Section: Implications For Music Educationmentioning
confidence: 99%
“…12 A survey of 940 students who participated in modern band classes in a New York City program demonstrated significant increases in students' self-reported abilities to play these instruments at the end of the year. 13 In 2019, the NAfME annual conference featured an All-National Honors Modern Band for the first time, demonstrating that this experience is widely recognized as a school music ensemble. Sixteen students participated in this inaugural ensemble, including four vocalists, three guitarists, three pianists, three bassists, and three percussionists.…”
Section: What Is Modern Band?mentioning
confidence: 99%
“…Still, K-12 popular music education is a growing movement in the United States, due in part to efforts of nonprofit organizations like Little Kids Rock, a charity that helps school establish modern band programs through training workshops and instrument grants (Powell, Krikun, & Pignato, 2015). For the first time in 2019, the National Association for Music Education (NAfME) will feature a Modern Band ensemble as part of its All-National Honor Ensembles (NAfME, 2019), and professional organizations and journals such as the Association for Popular Music Education, the Journal of Popular Music Education, and NAfME's Popular Music Education Special Interest Research Group are available to provide support and resources for teachers of modern band (Weiss, Abeles, & Powell, 2017). Acquiring instruments for use in the modern band ensemble is one of the greatest challenges to initiating popular music education programs.…”
Section: Modern Bandmentioning
confidence: 99%